Tallennusmedian suorituskyvyn vaikutus Wordpress-julkaisujärjestelmän toimintaan - Rantakömi, Matti (2024)
Wordpress is a Content Management System, which is used as a platform for web services, such as websites, online stores and blogs. It's by far the most popular Content Management System in the world. Web service performance has a decisive effect on the user experience, so the service should work as quickly as possible in all situations, even during peak traffic. Slowly responding service is one of the biggest factors driving visitors away. In this thesis, the response times of the Wordpress Content Management System on virtual machine platforms equipped with different performance levels of hard disks was investigated using a constructive research method. The performance consists of several factors, such as speed of the memory, processors and storage system used on underlying hardware. The aim was to find out and compare their performance on different platforms. Test environment consisted of three virtual machines equipped with different levels of hard disk and CPU capacity were set up as test environments, on which the Wordpress web service with test content was installed. Fourth virtual machine with Locust load testing software installed were used to perform the actual measurements. In the first stage of the performance measurement, the front page of the Wordpress web service is loaded by a single user without the Linux Page Cache cache. The second test is done with the cache, starting with one user, after which the number of users is steadily increased up to 300 users. Graphs are compiled from the medians of page loading times, from which it's easy to observe the development of loading times. In the tests of the second measurement phase, a PHP script is loaded, which reads the same files from the disk as when loading the Wordpress front page, but doesn't execute the PHP code. In this way, the time spent just reading files from the hard disk can be observed. The measurement results were largely in line with what I thought. The load times of the test virtual machine with the slowest hard drive and the lowest CPU capacity were the slowest. This was especially emphasized in measurements made without a cache. Correspondingly, the results of test virtual machines equipped with faster hard drives and larger CPU capacities were significantly faster. When repeating the same test, the results obtained were consistent with the previous tests and the dispersion of the results between test rounds was small.